Factors Influencing Youth’s Brand Buying and Sharing: A Social Media (Twitter) User’s Perspective - Almarzoqi, Shaima Abdalla; Ajmal, Mian; Alshurideh, Muhammad Turki (International Review of Management and Marketing, 2025)
This study aims to investigate the impact of social media marketing platforms (Twitter) on the youth’s brand buying and sharing. The study uses a set of social media and mainly Twitter to study how social network users share their opinions and buy well know brand products. The study uses youth’s brand awareness, intention, interest, and brand knowledge. The study employed the survey approach to examine the study variables and test its hypotheses. A questionnaire was designed to collect data from UAE students and the target of this study was 388 responses were seen valid to be used to analyse the data collected. The study findings confirmed the growing significance of social media marketing using Twitter on youth’s brand buying and youth’s brand sharing. Additional sections are offered about the study implications and future research directions.